2007
DOI: 10.1074/jbc.m700809200
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide-dependent Allostery within the ABC Transporter ATP-binding Cassette

Abstract: ATP-binding cassette (ABC)3 transporters couple hydrolysis of ATP to vectorial translocation of substrates across cellular membranes, typically against a concentration gradient. These integral membrane proteins are involved in the transport of a wide range of substrates, including ions, sugars, amino acids, peptides, proteins, lipids, and xenotoxins, and form one of the largest protein families across all species (1). Many ABC transporters are central to important biomedical problems, including resistance of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
73
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(91 citation statements)
references
References 55 publications
15
73
2
1
Order By: Relevance
“…In addition, structural comparisons of isolated NBDs reveal a putative motion within each NBD, characterized by a rotation of the α-helical subdomain relative to the RecA-like subdomain upon ATP binding and hydrolysis (5)(6)(7)(8). This motion is also supported by molecular dynamic studies (10,11) and the rotation is suggested to transmit conformational changes to the transmembrane domains (16). Interestingly, the helical subdomain (14,39) is the most variable region of the NBDs (40,41) and might have evolved to accommodate the structural constraints imposed by the TMDs in ABC transporters.…”
Section: Outward Rotation Of the α-Helical Subdomain In The Intact Masupporting
confidence: 48%
See 1 more Smart Citation
“…In addition, structural comparisons of isolated NBDs reveal a putative motion within each NBD, characterized by a rotation of the α-helical subdomain relative to the RecA-like subdomain upon ATP binding and hydrolysis (5)(6)(7)(8). This motion is also supported by molecular dynamic studies (10,11) and the rotation is suggested to transmit conformational changes to the transmembrane domains (16). Interestingly, the helical subdomain (14,39) is the most variable region of the NBDs (40,41) and might have evolved to accommodate the structural constraints imposed by the TMDs in ABC transporters.…”
Section: Outward Rotation Of the α-Helical Subdomain In The Intact Masupporting
confidence: 48%
“…Each NBD consists of a RecA-like subdomain, found in numerous ATPases (4), and an α-helical subdomain that is specific to the ABC family (5). Crystallographic studies (5)(6)(7)(8) and molecular dynamic simulations (9,10), performed on isolated NBDs, suggest that the helical subdomain rotates toward the RecA-like subdomain in response to ATP binding. This rotation positions the ABC family signature motif to interact with nucleotide across the dimer interface so that the NBDs can close to hydrolyze ATP.…”
mentioning
confidence: 99%
“…However, it has been shown that some of these transporters can be partially uncoupled in reconstituted systems [81,82]. A quest to understand the uncoupling process has led to extensive evidence that the two NBDs bind and hydrolyze ATP in a cooperative manner [83][84][85][86].…”
Section: Putative Catalytic Mechanism Of Abc Transporters Of the "Expmentioning
confidence: 99%
“…2) Constant contact model. The NBDs remain in contact during the hydrolysis cycle, and the power stroke results from smaller conformational changes at the NBD-dimer interface (8,(13)(14)(15)17).…”
Section: Abcmentioning
confidence: 99%